Presentation and Intraoperative Findings of Penetrating Abdominal Injuries in a Battle Field Hospital, Yemen 2018 – 2019 - Adam, Ayman Fadul Ebad; Ahmed, Mohamed El Makki (Gezira Journal of Health Sciences, 2020)
Background Abdominal war wounds have the strange history of all injuries suffered in times of armed conflict. Of all major life threatening injuries, wounds in the abdomen are ---      --the most amenable to surgical intervention likely to produce good results and the return of the patient to a productive life. Most patients with blunt and penetrating trauma were treated conservatively and surgically respectively. The cure rate is higher in surgical than in conservative management. Objective this study aimed to describe the presentation and intraoperative findings in penetrating abdominal injury in battle field hospital, Yemen War, 2018 – 2019 Methods An Observational, descriptive, hospital based cross sectional study was conducted in Field Hospital in Yemen within the period from September 2018 to March 2019. Data entered, cleaned and analyzed using SPSS version 25.0. Results This study covered 80 study participants. The majority of them were classified as military personnel (91.2%).. The majority of them were males with male: female ratio of 19: 1 with ages ranging from 10 to 53 years and a mean ± SD of 31.7 ± 9.9 . Our study found that two thirds of the patients had gun shots (66.3%), blast injury (16.3%), explosive injury (15%) and sharpness among only (8.8%). The average time from injury to laparotomy was less than one hour in more than three quarters of the study participants (80%). Concerning the presentation of the study participants, half of them (51.3%) were shocked, (21.3%) evisceration, and (61.4%) reported peritonism presentation. Nearly two thirds of the patients showed inlet only (65%), while (22.5%) presented with both inlet and outlet and only (12.5%) lost part of their abdominal wall. More than half of the study participants received Medical help outside the battle field hospital (53.8%), such as blood transfusion (53.5%) and intravenous fluids for the majority of them. Regarding the intraoperative findings, the majority of the patients (95%) had operated, on average, for five hours or less. Nearly half of them had been injured in 1 – 3 organs (45%) while (7.5%) of them was injured in more than six organs. The most affected organs were Jejunum (75.6%), Ileum (73.1%), and large colon (43.6%),while the liver and splenic injuries were(32.1%) and (17.9%) respectively . Furthermore, cardiac arrest occurred only among a small proportion (2.5%) of the study patients. Only (1.3%) mortality reported. Only (1.3%) had reactionary bleeding as an early post-operative complication among our study patients. Finally, our study realized that most of the patients (83.7) were evacuated within 6 to 12 hours. Conclusion and recommendation The majority of patients with abdominal gunshot wounds are best served by laparotomy; however, select patients may be managed expectantly. All cases of such injuries should have exploratory laparotomy as soon as possible with a short time interval between the injury and the operation to prevent morbidity and mortality.